'Diagnosing food protein‐induced enterocolitis syndrome'. Issue 1 (3rd November 2020) - Barni, Simona; Vazquez‐Ortiz, Marta; Giovannini, Mattia; Liccioli, Giulia; Sarti, Lucrezia; Cianferoni, Antonella; Mori, Francesca
Abstract: Food protein‐induced enterocolitis syndrome is still a mysterious disease, pathogenically poorly characterized, although the first FPIES case has been described in 1967. Mainly, food protein‐induced enterocolitis syndrome diagnosis is based on clinical history. The oral food challenge remains the gold standard to confirm the diagnosis, especially in particular situations. Although there are no diagnostic laboratory or imaging tests which are specific for diagnosis, they could, however, sometimes be helpful to rule out clinical conditions which are similar to food protein‐induced enterocolitis syndrome reactions. The purpose of this review is to define the clinical features of FPIES and to summarize the current available tools for the diagnosis of FPIES. This review is intended to be a practical guide for the clinician facing a patient with food protein‐induced enterocolitis syndrome avoiding delayed diagnosis with unnecessary laboratory tests and detrimental treatments. Moreover, it highlights the unmet needs in diagnosis that require urgent attention from the scientific community to improve the management of patients with FPIES.